Beyond Financial Resources: Analyzing the Determinants of Export Activities of Emerging Market Social Enterprises. Issue 3 (3rd July 2021) - Godinez, Jose; Sanchez-Barrios, Luis Javier; Lopez-Gomez, Sara; Gomez-Nuñez, Liyis
Abstract: Social enterprises pursue social and economic goals simultaneously, but little is known about how they start an exporting strategy, especially if they are from emerging markets. We examined the determinants of exports of 522 emerging markets social enterprises (EMSEs) from Colombia. Based on a quantitative approach, our results show that EMSEs leverage their resources to start export operations if, in addition to capital, they leverage their structural and experiential resources. Structural resources include externally validated accounting and financial books, process certifications, and exposure in trading shows; experiential resources include the firm's staff having primary education.